MRR Filter Characterizations In WDM System For Digital Signals Transmissions - Hazura, Haroon; Nurul Nadia, Abd Aziz; Hanim, Abdul Razak; Anis Suhaila, Mohd Zain; S. K., Othman; Fauziyah, Salehuddin (Penerbit Universiti, UTeM, 2016)
This paper discusses the implementation, capabilities and limitations of Microring Resonator (MRR) filter in the Wavelength Division Multiplexing (WDM) system, particularly as a wavelength selector components for high-speed (> 2.5 Gbps) WDM digital systems. To accommodate the demand for telecommunications traffic growth, WDM technique is widely used in optical communication networks to grant for more information to be shared through the same physical transmission channel. In general, the performance of the system in terms of bit error rate (BER) and system quality factor (Q) is described. The performance of WDM system with MRR filter as the wavelength selector has been studied for the first time in this paper.